2022
DOI: 10.2340/17453674.2022.4537
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab prevents acetabular bone loss around an uncemented cup: analysis of secondary outcomes in a randomized controlled trial

Abstract: Background and purpose: Uncemented total hip arthroplasty (THA) is associated with periprosthetic bone loss. In a secondary outcome analysis from a randomized controlled trial, we studied whether denosumab can prevent loss of acetabular periprosthetic bone mineral density (pBMD) in patients who received a trabecular metal cup during uncemented THA.Patients and methods: 64 patients (aged 35–65 years) with unilateral osteoarthritis of the hip were randomized to 2 subcutaneous injections with denosumab or placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Studies specifically centered on denosumab’s role in OA treatment were limited until a recent trial honed in on its application specifically for managing erosive hand OA[ 40 ]; however, some studies suggest that it can affect bone and cartilage positively and negatively. An analysis of secondary outcomes of an RCT found that administration of denosumab 1–3 days after surgery and 6 months after surgery prevented acetabular bone loss around an uncemented cup placed during total hip arthroplasty [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies specifically centered on denosumab’s role in OA treatment were limited until a recent trial honed in on its application specifically for managing erosive hand OA[ 40 ]; however, some studies suggest that it can affect bone and cartilage positively and negatively. An analysis of secondary outcomes of an RCT found that administration of denosumab 1–3 days after surgery and 6 months after surgery prevented acetabular bone loss around an uncemented cup placed during total hip arthroplasty [ 41 ].…”
Section: Resultsmentioning
confidence: 99%